Molecular Dynamic Studies and Experimental Methods for Dispersion of Graphene Sheets with Different Strategies - Ahmadin, Hashem; Zare, Karim; Monajjemi, Majid; Shamel, Ali (Revista de la Universidad del Zulia, 2020)
Graphene sheets tend to self-associate in microscale aggregates. This occurs in products with less mechanical and electrical action. Recognizing this problem, extensive research has been evidenced in the literature on the development of dispersion technologies, based on both mechanical and chemical approaches. Chemically converted sheets wrapped in surfactants, the ability of surfactants to disperse graphene nanospheres in a medium, was evaluated by different research groups, using both experimental and molecular dynamics (DM) simulation methods; In this article we summarize these methods and techniques. The effect of the influencing factors that count the ions, the pH value and the surfactants in the separation and agglomeration of the gerata sheets is highlighted. Here, we reviewed the recent advances that have been made in the dispersion of graphene sheets in aqueous and organic media by non-covalent adsorption of surfactants and polymers. Graphene structure, properties, and mainly self-assembly are also studied.